Anomali gigi sebagai sarana identifikasi forensik - Icha Artyas Annariswati; Shintya Rizki Ayu Agitha (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: The identification process is very important to determine the identity of the corpse. Identification through teeth is a primary identification method that is often used because teeth have a high degree of individuality. Identification through teeth can be analyzed through dental anomalies. Dental anomalies can assist in the identification process because of their uniqueness, stability, and high incidence in different populations. This paper aims to provide information on the importance of dental anomalies as a relevant and scientific means for identification purposes. Review: Dental anomalies can be defined as morphological abnormalities of the teeth that occur at the stage of growth and development of teeth. Dental anomalies are also inherited disorders that can occur as part of a syndrome. The wide variety of dental abnormalities in the form of size, number, morphology, structure or position of teeth in the oral cavity that can be possessed by each individual can be a characteristic of that individual. Conclusion: The use of dental anomalies in identification has been scientifically recognized with proper diagnosis and writing of dental anomalies in the medical record can be used for identification purposes in the forensic field.